Sosiologi Pluralisme dalam Pendidikan Agama Kristen: Upaya Membangun Kesatuan Bangsa - Yonatan Alex Arifianto; Andreas Fernando; Reni Triposa (Jurnal Shanan, 2021)
Indonesia has experienced religious conflicts and brought about alarming humanitarian impacts. The horizontal conflict has pushed into the joints of destroying the pillars of the nation's integrity. Moreover, conflict destroys harmony, therefore the author's aim was to describe pluralism through the perspective of Christian religious education as an effort to bring generations to continue to build the nation and maintain its integrity. The writing of this article used a descriptive qualitative method with a literature study approach related to the sociology of religious pluralism in the perspective of Christian religious education as an effort to build national unity. The findings of this study are firstly the sociology of pluralism starting from recognizing and understanding the nature of pluralism and understanding all the values ​​of pluralism. Second, all believers, especially teachers and students, see and understand that pluralism in the concept of Christian Religious Education is not contradictory to what is done by people and organizations that promote pluralism, but it needs to be emphasized that pluralism in agreement is only to maintain and build the integrity of the nation. Third, on this basis, Christianity, in this case the role of Christian religious education, must be actualized in social life in pluralism.